Bakalaura studentu piesaistes stratēģijas Latvijas augstskolās: Latvijas Universitātē, Rīgas Juridiskajā augstskolā, Stokholmas Ekonomikas augstskolā Rīgā - Zeidaka, Santa (Latvijas Universitāte, 2016)
Maģistra darba mērķis ir balstoties uz veikto analīzi maģistra darbā dot priekšlikumus mārketinga aktivitāšu uzlabošanai Latvijas augstskolām. Lai nāktu klajā ar priekšlikumiem darba autore veica sekojošus uzdevumus: 1.Balstoties uz teorētisko bāzi tika analizētas veiksmīgākās izmantotās mārketinga metodes studentu piesaistē; 2.Tika analizētas augstskolu izmantotās mārketinga aktivitātes studentu piesaistē; 3.Ar intervijas metodi tika iepazīti augskolu mārketinga speciālisti, kuri sniedza informāciju par ikgadējo mārketinga aktivitāšu organizēšanu; 4.Ar aptaujas metodi tika izpētīts, kuri reklāmas izplatīšanas līdzekļi ir veiksmīgākie, lai piesaistītu topošos studentus. 5.Analītiskās daļas noslēgumā tika salīdzinātas trīs augstskolu mārketinga aktivitātes, kā arī sniegti priekšlikumi. Darba apjoms ir 108 lapas puses, darbā iekļauti 19 attēli, 2 tabulas un pieci pielikumi.

The aim of the present Master’s Paper is to make recommendations for the improvement of marketing activities to the higher educational establishments of Latvia on the basis of the analysis, which has been conducted throughout the Master’s thesis. In order to present the recommendations, the author of the paper performed the following tasks: 1.By relying on the theoretical basis, the most successful marketing methods that had been used to attract the students, were analysed; 2.The analysis was conducted regarding the marketing activities that had been used by the higher educational establishments to attract the students; 3.Through the interview method, the author got acquainted with the marketing specialists in the higher educational establishments, who provided the information about the organisation of the annual marketing activities; 4.Through the survey method, the author researched into the most successful advertising means for the students’ attraction. 5.In the conclusion of the analytical part the marketing activities of three higher educational establishments were compared, as well as the recommendations were made. The present paper consists of 108 pages and includes 19 images, 2 tables and five attachments
The comparison of marketing strategies in higher education institutions in Latvia: University of Latvia, Riga Graduate school of Law, Stockholm School of Economics in Riga
Keywords: Vadībzinātne; students; augstskola; augstskolu mārketings; Rīgas Juridiskā augstskola; Stokholmas ekonomikas augstskola Rīgā